Formamidinium halide salts as precursors of carbon nitrides. (30th August 2022) - Ciria-Ramos, Isabel; Navascués, Nuria; Diaw, Fatou; Furgeaud, Clarisse; Arenal, Raul; Ansón-Casaos, Alejandro; Haro, Marta; Juarez-Perez, Emilio J.
Abstract: Pyrolysis of formamidinium halide salts (FAI, FABr) results in a new type of amorphous carbon nitride materials with a mass fraction of 40–50% nitrogen content. Pyrolysis temperature drives final chemical composition, morphology, optical and electrical properties of the material independently of the halide precursor and identifying triazine ring, instead of typical heptazine unit, as the main building block of this material. We elaborated a temperature dependent mechanism of formation for these materials and foresee its potential value as native passivation layer in the field of perovskite solar cells. Graphical abstract: Image 1